Zelotes wunderlichi, a replacement name for the preoccupied ground spider Zelotes turcicus Wunderlich, 2011 (Araneae, Gnaphosidae) - Blick, Theo (Zootaxa, 2017)
In the World Spider Catalog (WSC 2017) the formerly overlooked species Zelotes turcicus Seyyar, Demir & Aktaş, 2010 was recently added. Thus Zelotes turcicus Wunderlich, 2011 is a primary homonym and requires a new name. The author informed Jörg Wunderlich who approved the present author to carry out this formal renaming (without suggesting a new name): for Zelotes turcicus Wunderlich, 2011 the replacement name Zelotes wunderlichi nomen novum is herewith proposed.